Does Agricultural Productivity Drive Economic Growth? Evidence from Developed and Developing Countries within the RCEP Bloc - THONG, Ching Ling; BIN ARIP, Mohammad Affendy; THONG, Chien Ling (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025DO - 10.14505/tpref.v16.3(35).21, 2025)
This study explores the relationship between agricultural productivity and economic growth across Regional Comprehensive Economic Partnership (RCEP) member countries from 2001 to 2024, providing a novel focus on this economic bloc. Employing advanced econometric techniques, including panel unit root tests, Autoregressive Distributed Lag (ARDL) models, panel dynamic Ordinary Least Squares (DOLS), and panel threshold models, the analysis reveals contrasting dynamics between developed and developing economies. Key findings include the dual impact of agricultural total factor productivity (AgTFP) is positive in developing countries and negative in developed ones and the role of the incremental capital-output ratio (ICOR), which fosters growth in developing economies but impedes it in developed ones. The prevalence of undernourishment consistently hinders economic growth across all models, while employment in agriculture exhibits divergent effects, positively influencing growth in developing nations but negatively in developed ones. The results underscore the critical role of improving agricultural productivity in fostering economic growth in developing countries, highlighting the need for government interventions in areas such as credit access, training programs, infrastructure development, and market expansion. Conversely, for developed nations, the diminishing contribution of agriculture to GDPPC suggests a need for technological innovation and diffusion to sustain productivity gains. This research uniquely contributes to understanding the nuanced role of agriculture in economic growth within the RCEP framework.